RESPON PASAR TERHADAP PENGUNGKAPAN AKUNTANSI: TINJAUAN LITERATUR SISTEMATIS GLOBAL - Muflikhah, Itsna; Rukmana, Risa (Universitas Islam Negeri Alauddin Makassar, 2026)
This systematic literature review (SLR) examines how capital markets respond to accounting disclosures globally, analysing 39 open access Scopus indexed articles (2016–2026) via the PRISMA 2020 protocol. Three analytical dimensions are investigated: (1) institutional context developed versus emerging markets; (2) disclosure type mandatory versus voluntary; and (3) dominant methodology. Findings show that value relevance models (Ohlson) and event study methods dominate the literature. Developed market firms exhibit stronger disclosure price relationships than emerging market counterparts, where concentrated ownership and weak governance attenuate information transmission. Voluntary sustainability and CSR disclosures produce heterogeneous market reactions contingent on disclosure quality and credibility. Governance mechanisms, information asymmetry, and regulatory environment are identified as critical moderators. The review synthesises global evidence, identifies research gaps, and provides a roadmap for future inquiry in developing country contexts.